1989
DOI: 10.1177/106002808902301001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Propofol: An Intravenous Anesthetic Agent

Abstract: Propofol is a 2,6-diisopropylphenol with sedative-hypnotic properties. Because of its slight solubility in water, the drug is formulated as an emulsion for clinical use. It is highly lipophilic and distributes extensively in the body. The blood concentration-time profile of propofol after an iv bolus injection follows a three-compartment model with half-lives of 2-4 min, 30-45 min, and 3-63 h, respectively. Propofol is extensively metabolized by the liver prior to its elimination by the kidney. Following an iv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 63 publications
(6 reference statements)
1
33
0
1
Order By: Relevance
“…Decreases in blood pressure with propofol anesthesia are thought to be due in part to inhibition of sympathetic tonus (23). Propofol can also cause decreases in systemic vascular resistance, myocardial blood flow, and oxygen consumption, possibly through direct vasodilation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in blood pressure with propofol anesthesia are thought to be due in part to inhibition of sympathetic tonus (23). Propofol can also cause decreases in systemic vascular resistance, myocardial blood flow, and oxygen consumption, possibly through direct vasodilation (24).…”
Section: Discussionmentioning
confidence: 99%
“…The animals in our study received high doses of propofol during the procedure (total, 11.4 mg/kg for S473 and 14.5 mg/kg for S468). Propofol is well known for its ability to cause a decrease in blood pressure in humans (Grounds et al, 1985;Larijani et al, 1989;Muzi et al, 1992;Robinson et al, 1994Robinson et al, , 1997 as well as in dogs (Musk et al, 2005). In the latter study, four groups of 20 dogs each received propofol to establish blood propofol concentrations of 2.5, 3.0, 3.5, and 4.0 mg/ml.…”
mentioning
confidence: 97%
“…12,13 However, this agent occasionally decreases systemic vascular resistance, cardiac contractility, and ultimately cardiac output without a concomitant change in heart rate, and respiratory depression can also occur. 5,14,15 Recently, several studies have revealed most adverse events associated with propofol sedation were mild and often transient during advanced interventional endoscopic procedure. 12,[16][17][18] A randomized study in Japan, which compared continuous propofol infusion with intermittent midazolam injection during ESD for EGC, found that propofol is a safe and effective sedative agent and that patients treated with propofol had a quicker recovery than those who were treated with midazolam.…”
Section: Discussionmentioning
confidence: 99%